Children’s birth weight and the risk of general obesity and central obesity in primary school children: a 4-year longitudinal study - Yi Lin; Richard Rankin; Stuart McDonald; Xiao-Yong Li; Feng Wang; Si-Jia Wang; Qing-Hai Gong; Feng Tong (Frontiers in Public Health)
BackgroundChildhood overweight (OW) and obesity (OB) have become a serious public health concern worldwide. The objective of this study is to investigate the association between the levels of birth weight (BW) and OB and central OB in Chinese primary school children.MethodsA school-based longitudinal study was conducted from 2016 to 2019. Information of children and parents were gained from both children and parents’ questionnaires. Longitudinal anthropometric data were obtained from annual health check. BW (kg) was categorized into 4 groups [<3.0, 3.0–3.4, 3.5–3.9 and ≥ 4.0 (macrosomia)]. Normal weight, OW and OB were defined based on sex-specific and age-specific body mass index (BMI). Central OB was identified using sex-specific waist-to-height ratio (WHtR).ResultsAround 14.5 and 15.6% of 1,204 children had low BW (<3.0 kg) and macrosomia, respectively. The overall rate of OB and central OB at 7–10 years were 10.4 and 28.3%, respectively. Linear-shaped relationships were observed between BW and anthropometric values in both sexes at 7–10 years and 11–13 years. A J-shaped relationship was found between BW and WHtR in boys at 11–13 years. Higher BW status were associated with increased adjusted odds of OB in children (3.5–3.9: OR: 1.5, CI 95%: 1.1–2.0; macrosomia OR: 1.4, CI 95%: 1.0–2.0).ConclusionHigher levels of BW (≥ 3.5 kg) were associated with an increased risk of OB in children, but not central OB. The results can support public health specialists for future research and improvement of strategies for childhood obesity prevention.